2003
DOI: 10.1046/j.1439-0531.2003.00404.x
|View full text |Cite
|
Sign up to set email alerts
|

Meiotic Response of In vitro Matured Canine Oocytes under Different Proteins and Heterologous Hormone Supplementation

Abstract: The impact of TCM-199 supplemented with different proteins and heterologous hormones on the in vitro maturation (IVM) rate of bitch oocytes was evaluated by nuclear staining under fluorescence microscopy. Oocytes were recovered by slicing of ovaries from bitches presented at various stages of oestrous cycle to ovariohysterectomy. The basic culture medium was TCM-199 supplemented with 25 mM Hepes/l, with 10% heat-inactivated oestrous cow serum (ECS), 50 microg/ml gentamicin, 2.2 mg/ml sodium bicarbonate and 22-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0
1

Year Published

2003
2003
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(27 citation statements)
references
References 24 publications
(37 reference statements)
1
25
0
1
Order By: Relevance
“…Since we need to establish optimal culture period which gives as much as the MII oocytes higher developmental competence at the same time for in vitro fertilization and somatic cell nuclear transfer, our protocol will be useful for evaluation of the quality of canine oocytes matured in vitro. Under our culture conditions, the percentage of oocytes that reached the MII stage was not high, which suggests that further improvements in IVM of canine oocytes are required, including further examinations of factors previously reported [4,5,7,8,12,16]. In such studies p34 cdc2 kinase and MAPK assays used in the present study will be good indicators for evaluation of nuclear and cytoplasmic maturation of oocytes.…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…Since we need to establish optimal culture period which gives as much as the MII oocytes higher developmental competence at the same time for in vitro fertilization and somatic cell nuclear transfer, our protocol will be useful for evaluation of the quality of canine oocytes matured in vitro. Under our culture conditions, the percentage of oocytes that reached the MII stage was not high, which suggests that further improvements in IVM of canine oocytes are required, including further examinations of factors previously reported [4,5,7,8,12,16]. In such studies p34 cdc2 kinase and MAPK assays used in the present study will be good indicators for evaluation of nuclear and cytoplasmic maturation of oocytes.…”
Section: Discussionmentioning
confidence: 62%
“…Many researchers have reported the in vitro maturation (IVM) of canine oocytes, and the discussion in the literature now focuses on how to improve development. For example, the age of the donor bitch [3], oocyte diameter [4,5], protein [6][7][8][9][10] and hormonal supplementation of maturation media [11][12][13][14][15][16] have all been examined. However, the proportion of MII oocytes remains low (0-43.4%) [9,[15][16][17][18][19][20], and a number of essential issues have yet to be resolved.…”
mentioning
confidence: 99%
“…The influence of protein supplementation on cultured dog oocytes has been examined extensively, albeit with conflicting results (Hewitt et al, 1998;Bolamba et al, 2002;Rodrigues and Rodrigues, 2003a). Hewitt et al (1998) demonstrated that supplementing culture media with 0.3% bovine serum albumin (BSA) or 10 to 20% fetal bovine serum (FBS) appeared optimal for dog oocyte maturation when TCM 199 was the culture medium.…”
Section: Protein Supplementationmentioning
confidence: 99%
“…There are several reports indicating the role of media in vitro supplements on the meiotic maturation competence of canine oocytes (Otoi T et al 1999, Rodrigues and Rodrigues 2003, Cui et al 2006). However, the in vitro maturation procedures still bring low efficiency and only 15-20% of bitch oocytes reach the MII stage.…”
Section: Selected Aspects Of Canine Oocytes Maturation With Relation mentioning
confidence: 99%
“…A similar mechanism may determine the oocytes receptivity to each hormone or growth factor that may have various effects on oocytes maturation. Additionally different molecules (in most cases there are polypeptides) may extent different effects on signal metabolic pathways that lead to reach a full developmental competence by oocytes (Rodrigues and Rodrigues 2003).…”
Section: Introductionmentioning
confidence: 99%